The National Health Service - Great Britain. Central Office of Information. (London : His Majesty's Stationery Office, 1948)
1948 1948 1940s 38 pages The Service is therefore planned, and managed, by a partnership of local bodies of adequate size working together under the general guidance of the Ministry. There must be an equally close partnership between all these authorities on one hand, and the doctors with the rest of the army of health workers on the other. The doctors themselves (and, to a lesser extent, the other health workers) have a direct and ample share in the making of all plans and all business arrangements and in the daily running of the services. The problem of local control of the new Health Service has been met by dividing England and Wales into fourteen large regions, each of which contains a single hospital service authority (the Regional Hospital Board), and into 146 districts — the areas of the counties and county boroughs, whose councils have become the Local Health Authorities within those areas. The health services themselves are divided into three main branches : (1) the hospital and specialist services ; (2) a group of local government services ; and (3) a group of family practitioner services including those of the family doctor and dentist. The hospital and specialist services, then, are administered by the new Regional Boards. The major local authorities (sixty-two county councils and eighty-three county borough councils)* administer the local government services, each authority employing a medical officer of health and working through a health committee of the council. The general medical services are those of three independent experts — the family doctor, the dentist, and the ophthalmic doctor or ophthalmic optician — aided by the chemist and the dispensing optician. These general medical services are administered by new local bodies called the Executive Councils, each of which covers the area of one major local authority (with a few exceptions, where two such areas are administered together). There is no change in the arrangements which were in force before the Act for medical research and medical education, and no Government interference with either. Under the scheme the finance and administration of the teaching hospitals are separated from those of the medical schools, which are assisted by money provided by the University Grants Committee. It should be explained that the more detailed (but far from complete) account of the National Health Service which is given in the following chapters refers only to England and Wales; there is a separate Act, although on similar lines, for Scotland. * The Council of the Isles of Scilly is also a Local Health Authority. 8 21/1489